2017
DOI: 10.3126/ajms.v8i5.17723
|View full text |Cite
|
Sign up to set email alerts
|

Study of effects of Sudarshan Kriya on Postmenopausal symptoms among central India women population : A preliminary study

Abstract: Background: Menopausal health concerns mainly include the vasomotor symptoms, cardiovascular symptoms, osteoporosis, cancer, sexual problems and urogenital atrophy. Our life style today leads to a lot of stress, depression and anxiety. Prolonged stress can make one experience the symptoms like menopause (though not actually inducing it).Yoga exercise meditation and life style modification have relieved stress and enhanced the quality of life. Sudarshan Kriya (SK) is a rhythmic breathing technique with 4 breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…25 Hence, it is suggested that yoga breathing-related intervention like SKY can improve the menopause symptoms-related quality of life equivalent to other proven yoga interventions. 26,27 The menopausal women in the present study who practiced for 1-year brisk walking demonstrated no significant decreased in the perception of climacteric symptoms. Whereas regular aerobic exercise or equivalent physical activity of different types has been found to be beneficial in climacteric women experiencing vasomotor symptoms.…”
Section: Discussioncontrasting
confidence: 49%
“…25 Hence, it is suggested that yoga breathing-related intervention like SKY can improve the menopause symptoms-related quality of life equivalent to other proven yoga interventions. 26,27 The menopausal women in the present study who practiced for 1-year brisk walking demonstrated no significant decreased in the perception of climacteric symptoms. Whereas regular aerobic exercise or equivalent physical activity of different types has been found to be beneficial in climacteric women experiencing vasomotor symptoms.…”
Section: Discussioncontrasting
confidence: 49%
“…Postmenopausal symptoms among women from central India and concluded that Initiating Sudarshan Kriyas into the lives of postmenopausal women at the right time can assure a less morbid, more comfortable and a better quality of postmenopausal life [10] which is also in favour of our study. Vinayak P. Doijad et al (2013) did a study on Effect of Yogic exercises on aerobic capacity (VO2 max) and concluded that yoga practice can be used to perk up cardiorespiratory fitness [11] , which support our result.…”
Section: Rajeshree Tukaram Et Al (2023) Did a Study On Study Of Effec...mentioning
confidence: 76%